Ubiquitous computing: a learning system solution in the era of industry 4.0 - Wildan Toyib; Delvis Agusman; Hari Ramza (Jurnal Informatika, 2020)
Ubiquitous computing, which was initially advocated by Mark Weiser has become one of the keywords to express a vision of the near future of computing systems. The "ubiquitous world" is a ubiquitous computing environment with integrated networks; computer integrated manufacturing system (CIMS) and invisible computers which equipped sensor microchips and radio frequency identification systems. Anyone can access the ubiquitous computing systems anytime and anywhere broader, without individual awareness or skills. Ubiquitous computing is becoming crucial elements to organize the activities of groups of people by use of groupware under workforce mobility. The computer-supported cooperative work is transforming from telework to ubiquitous work with new information and communication technologies that support people working cooperatively. Ubiquitous learning is a demand for the knowledge workforce for more multi-skilled professionals. It is a new and emerging education and training system that integrating e-learning of cyberspace and mobile learning of physical space with a global repository that has the potential to be accessed by anyone at any place and anytime under ubiquitous integrated computing environment. In this paper, we discuss the study of emerging trends through the implementation of work and learning that influenced ubiquitous computing technology prospects. Furthermore, the perspective of ubiquitous work and learning system, gaining quality, and hence credibility with emerging information and communication technologies in education and training systems in the area of the education system are discussed. The experimental results showed that CIMS could improve the students learned more efficiently and achieved better learning performance.